Scotian inspirations in Immanuel Kant’s transcendentalism - Surzyn, Jacek (Folia Philosophica, 2011)
The paper deals with important problem of a parallel between the notion of transcendentalism in Johan Duns Scotus and Immanuel Kant. For it might be argued that it is possible to point out at least some Scotian inspirations in Kant. Kant worked in the intellectual atmosphere influenced by Scotus, especially his notion of metaphysics as transcendental science (scientia transcendens), followed then by F. Suarez and Ch. Wolff, and the latter had a great influence on Kant. This paper provides a set of arguments from indirect proofs based on the parallel in Scotus and Kant. Despite of the fact that in cases like this one it is impossible to call for certainty, the conclusions seem to be hard to invalidate.